Predictors Influencing Indigenous Learners’ Academic Performance - Prudente, Neil; Torres, Maria Zorayda (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the predictors influencing the academic performance of Indigenous learners in selected public secondary schools in Quezon Province. Guided by theories such as Self-Determination Theory, Social Cognitive Theory, Constructivist Learning Theory, Ecological Systems Theory, and Culturally Responsive Pedagogy, the research explored how learner-related, instructional, and socio-cultural factors affect Indigenous learners’ educational experiences and academic outcomes. The study utilized a quantitative descriptive-comparative research design involving 50 Indigenous learners from Grades 7 to 10 during the School Year 2025–2026. Data were gathered using a validated researcher-made survey questionnaire employing a 4-point Likert scale and analyzed through descriptive and inferential statistical tools, including Weighted Arithmetic Mean, Kruskal-Wallis H Test, One-Way ANOVA, and Post Hoc Tests. The findings revealed that Indigenous learners generally demonstrated Fairly Satisfactory to Satisfactory academic performance. Students’ interest, study habits, teaching strategies, instructional devices and materials, parental support and involvement, and community participation were identified as significant predictors influencing academic achievement. Learners showed higher engagement when instruction was culturally responsive, interactive, and connected to their lived experiences. Significant differences were also found between academic performance and several identified predictors, indicating that learner motivation, instructional practices, family support, and community involvement collectively shape academic outcomes. Based on the findings, the study proposed the Culturally Appropriate and Responsive Educational Support (CARES) Toolkit to strengthen culturally inclusive educational practices for Indigenous learners. The study supports Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable education for Indigenous communities and Sustainable Development Goal 10 (Reduced Inequalities) through efforts to address educational disparities among marginalized learners. The research contributes to educational, cultural, socio-economic, and community sustainability by encouraging culturally responsive instruction, strengthening school-community collaboration, and supporting the preservation of Indigenous identity and knowledge systems within formal education.